AB1356 Observed dosing and refill compliance in bio-naÏve and bio-experienced rheumatoid arthritis patients treated with golimumab. (23rd January 2014) - Ellis, L.; Haas, S.; Bolge, S.; Tandon, N.
Abstract : Background: Little information on dosing, and refill compliance in golimumab-treated patients with rheumatoid arthritis has been published. Objectives: This study reports golimumab (GLM) dosing and refill compliance observed in rheumatoid arthritis (RA) patients. Methods: This retrospective database analysis assessed GLM use in adult RA patients with ≥2 GLM prescriptions between 4/24/2009 and 12/31/2010; ≥1 RA diagnosis during the study period; continuous activity in the Source® LX database (≥6 months pre; ≥6 months post index prescription) and a 28-31 day GLM supply. Refill compliance was defined as refills occurring ± 1 week of the expected 28-31 day (d) interval. The percent of compliant GLM refill intervals and the percent of patients demonstrating refill compliance at the 6th GLM dose were assessed in the overall population and in bio-naïve/bio-experienced subgroups. Descriptive statistics were used to characterize the study population (mean ± SD, median, n and %). Results: A total of 1, 103 RA patients and 6, 432 GLM refill intervals were observed. The sample was 82% female; mean age of 53 years with 63% bio-experienced. A 50 mg GLM dose was found in 98% of all fills. The mean ± SD refill interval for the overall population was 35.7±22.0 d with a median of 31 d. Bio-experienced patients had slightly more frequent refill intervals (35.4±21.3 d) as compared to bio-naïve patients (36.3±23.0 d), but the median was 31 d in both subgroups. Refill compliance was observed in 80% of all intervals for the overall population. Refill compliance at the 6th GLM dose was achieved by 84% of patients overall. Conclusions: In this retrospective analysis of a large national administrative claims database, 98% of GLM doses were 50 mg with approximately once monthly refill intervals. Overall refill compliance was observed in 80% of all GLM refills and in greater than 80% of RA patients at the sixth GLM dose. Median refill interval and refill compliance appeared similar in bio-experienced and bio-naïve subgroups. Further study of these trends using additional data sources are desired to substantiate these preliminary findings. Disclosure of Interest: L. Ellis Employee of: Janssen Scientific Affairs, LLC, S. Haas Consultant for: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, N. Tandon Employee of: Janssen Scientific Affairs, LLC